Metode Multi-Criteria Decision Making (MCDM) untuk Rancang Bangun Sistem Informasi Pengambilan Keputusan Rekrutmen Dosen Unggul berbasis Web - Hadi, Abrar; M. Syahputra; Khair, Rizaldy (The Indonesian Journal of Computer Science, 2024)
Excellent Lecturers are human resources (HR) that are very necessary in the world of education so that they can educate students to become superior human resources. Apart from that, all universities in Indonesia play an active role in improving the quality of education. One important factor that determines the quality of education in higher education is the quality of the lecturers who teach. Excellent lecturers are lecturers who are sought after and needed by all universities. However, in reality, the lecturer recruitment process in educational institutions often experiences obstacles, such as inaccurate decisions, errors in decision making, and late decision making. This can affect the quality of education provided and the effectiveness of the educational institution itself. Therefore, selecting superior and qualified lecturers is very important. So, we need a decision support system to help the recruitment process for superior lecturers more effectively and efficiently. Manual decision making in the recruitment process is considered less objective and can result in decisions that are not in accordance with wishes. The Multi-Criteria Decision Making (MCDM) method is a method that can be used to assist decision making in deciding which superior lecturers to recruit. The urgency of this research is to help make decisions effectively and efficiently. The aim of this research is to build a decision support system for the lecturer recruitment process using the web-based Multi-Criteria Decision Making (MCDM) method.